Oscillation in second order functional equations with deviating arguments - Bhagat Singh (International Journal of Mathematics and Mathematical Sciences)
For the pair of functional equations (A)(r(t)y′(t))+p(t)h(h(g(t)))=f(t) and (B)(r(t)y′(t))−p(t)h(y(g(t)))=0 sufficient conditions have been found to cause all solutions of equation (A) to be oscillatory. These conditions depend upon a positive solution of equation (B).